Development of Monopoly Media Assisted by QR Code: Cultural Diversity of Java Island in Class IV IPAS Learning - Widyaningsih, Wulan Rahmawati; Saputra, Henry Januar; Wardana, M. Yusuf Setia (Mimbar Sekolah Dasar, 2025)
Learning media currently plays an important role in making learning activities more active, interesting, and enjoyable, especially when used in elementary schools. However, learning science in grade IV at SDN Jatibarang 03, Semarang City, has limited teaching media because teachers tend to use lecture and discussion methods. As a result, students' motivation and understanding are less than optimal, and learning is less than optimal. This study aims to produce learning media in the form of a QR Code-assisted Monopoly game exploring Java Island for the subject of Science and Mathematics, specifically the material on cultural diversity for fourth grade elementary school students. The research was carried out based on the Research and Development (RD) method. The research design was based on the ADDIE development model, which consists of five tags, namely analysis, design, development, implementation, and evaluation. Validity testing was carried out by subject matter and media experts, while the trial was applied to 20 students and fourth-grade teachers. Studies show that the media obtains a suitability score of 96% from the subject matter and media experts' assessment, with a category of “Very Suitable”. In addition, the results of the teacher and student response questionnaires showed scores of 100% and 99.5% with a rating of “Very Good”. With this in mind, the QR Code-assisted monopoly game exploring Java Island was deemed suitable for use in supporting IPAS learning in grade IV at SDN Jatibarang 03.